MEWUJUDKAN PENDIDIKAN TOLERANSI ANTAR-UMAT BERAGAMA DI KUDUS: BELAJAR DARI KONFLIK TOLIKARA PAPUA 1 SYAWAL 1436 H / 2015 M - Rosyid, Moh. (QUALITY, 2015)
Combustion Masjid Al-Muttaqin in Karubaga, Tolikara, Papua on 1 Syawal 1436 H / July 17, 2015 when Muslims perform prayers Eid is a barbaric act. The trigger for the riots are (1) the implementation of the seminar Day Spiritual Awakening (KKR) by the Evangelical Church in Indonesia (GIDI) which invited thousands of guests including from Israel intentional simultaneously on Eid al-Fitr. The activity was disturbed when local Muslims to worship in the open space and the use of loudspeakers, (2) Regulation Regency Tolikara which prohibits the establishment of places of worship in Tolikara besides group GIDI, although legislation is never informed the central government, (3) indicated their efforts to transfer issue that criminal acts (corruption) that local officials do not expose it to be examined thoroughly. Efforts must be realized that the same thing does not happen again in this country is to realize education tolerant in educational institutions of formal and informal, to optimize the role of communication forum of religious (FKUB), which is usually monopolized by the religious majority, to accommodate the aspirations of people across religions in one container interfaith dialogue with the capital despite awareness bersesama different creed.Pembakaran Masjid al-Muttaqin  di karubaga, kabupaten  Tolikara, Papua pada 1 Syawal 1436 h/ 17 juli 2015 tatkala umat islam melaksanakan salat idul fitri merupakan tindakan biadab. Pemicu kerusuhan tersebut adalah (1) pelaksanaan seminar kebaktian kebangkitan Ruhani (kkR) oleh Gereja injili di indonesia (GiDi) yang mengundang ribuan tamu termasuk dari israel disengaja bersamaan pada hari Raya idul fitri. kegiatan tersebut merasa terganggu bila muslim setempat beribadah di ruang terbuka dan menggunakan pengeras suara, (2) Perda Pemkab Tolikara yang melarang pendirian tempat ibadah di Tolikara selain kelompok GiDi, meski Perda tidak pernah diinformasikan pada pemerintah pusat, (3) terindikasi adanya upaya pengalihan isuagar tindakan kriminal (korupsi) yang dilakukan pejabat setempat tak terekspos untuk ditelisik secara tuntas. upaya yang harus diwujudkan agar hal serupa tidak terjadi lagi di negeri ini adalah mewujudkan pendidikan toleran di lembaga pendidikan formal dan informal, men- goptimalkan peran forum komunikasi umat beragama (fkub) yang selama ini lazimnya dimonopoli umat agama mayoritas, mewadahi aspirasi umat lintas agama dalam satu wadah dialog lintas agama dengan modal kesadaran bersesama meski beda akidah.